KONSEP DIRI PENYANDANG TUNA DAKSA DI KOTA PEKANBARU - Laora, Jumiati; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Every human in the world has a different self concept. Self concept is all aspects of our perception of ourselves that cover physical, social, and psychological aspects that are formed because of our past experience and our interactions with others. Physically disabled is a state of disrepair or disrupted by interference or obstacles in the form of bones, muscles and joints in normal functioning. This condition can be caused by illness, accident or it can also be caused by inborn. The theory used in this research is the theory of Symbolic Interaction as the main theory and the theory of phenomenology as the supporting theory. The purpose of this study is to determine how the self concept of disabled people in Pekanbaru. This study uses qualitative method research with phenomenological approach. The data for this research gathered through interview, observation, documentation and literature study. The five informants obtained through snowball sampling. The results of this study indicate that the self concept of disabled people in Pekanbaru is positive. Although initially some physically disabled people who were not born to be disabled awkward with the changes they felt.Keyword: Self Concept, Disabled, Pekanbaru City